Rapid quantification of ruthenium(ii) polypyridyl anti-cancer drugs using a selective ligand dissociation LC-MS/MS method. Issue 37 (28th August 2020) - Mehanna, Stephanie; Bodman-Smith, Kikki; Daher, Costantine F.; Khnayzer, Rony S.
Abstract : This study validates a rapid LC-MS/MS method for the quantification of Ru(ii ) bipyridyl complexes in biological matrices, using selective ligand dissociation. Abstract : Research on Ru anti-cancer drugs is on the rise with many complexes in clinical trials. Inductively coupled plasma-mass spectrometry (ICP-MS) has been the standard technique for bioanalytical studies on Ru and Pt complexes in biological media. Tedious ICP-MS methods rely on detecting and quantifying the element while lacking important structural information of the original complexes. Despite being equally sensitive, more accessible, and highly selective to the target species, liquid chromatography-tandem mass spectrometry (LC-MS/MS) has not been validated for the analysis of Ru drugs. Using USFDA guidelines, we report here the optimization and validation of a facile LC-MS/MS method for the detection and quantification of three Ru(ii ) polypyridyl complexes in cells, plasma, and urine matrices. Importantly, a fast (10 min), single-step procedure was efficient for both extraction and sample purification, and analytes were rapidly eluted over a 3 min simple isocratic run. Specific parent ions were differentially fragmented by tandem MS, thus forming a unique and rational ligand dissociation chemistry that exhibits high selectivity to the target species with no measurable interferences or matrix effects. The developed LC-MS/MS method was advantageous vis-à-vis the prototypical ICP-MS based techniques both in vitro and in vivo, paving the way for its utilization in elaborate cellular uptake, pharmacokinetics, and pharmacodynamics studies.